Does Globalization Reduce Poverty? Some Empirical Evidence for the Developing Countries - Paolo Fighini; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
In this paper we address a key issue in the current debate on economic development: the effect of globalization on poverty. We review the empirical evidence on the relationship between globalization (broadly defined) and within-country poverty in the Developing Countries (DCs). To measure globalization we use, among others, standard indices of trade openness, financial openness and privatization. To measure poverty we use both indices of relative and absolute poverty averaged over five and ten years. The use of relative poverty indices enables inquiry into a different dimension of poverty and provides additional information with respect to previous research. Both descriptive statistics and econometric analysis are used to sketch a few stylized facts in a very complex framework of relationships.
Keywords: 330